Developmental reading 2 - Bernardo, Alejandro S. (Manila, Philippines : Rex Book Store, 2015)
In the midst of changing times, technological advancements, and popularity of social media, a life skill remains to be of paramount significance --- reading. It is for this reason that the role of reading teachers in the educative process should be persistently amplified for they are instrumental in ensuring that the learners are armed with the necessary skills to cope with the potential demands of school, workplace, and local and global communities where the ability to read is more than a necessity.
Lesson 1. Reading: An Overview -- Lesson 2. Reading models at a glance -- Lesson 3. Emergent literacy -- Lesson 4. Reading readiness -- Lesson 5. Teaching beginning reading -- Lesson 6. The Four-Pronged approach to teaching beginning reading -- Lesson 7. Developing love for reading -- Lesson 8. Teaching vocabulary -- Lesson 9. Pre-reading strategies -- Lesson 10. During reading strategies -- Lesson 11. Teaching strategic reading -- Lesson 12. Post-reading strategies -- Lesson 13. Testing reading.
Includes bibliographical references and index.
Keywords: READING